The Impact of acne on the quality of life of the patients attending dermatology outpatient department at Nobel Medical College Teaching Hospital (Journal of Nobel Medical College, 2018)
Background: Acne is a very common distressing skin condition that affects multiple aspects of quality of life of an individual. It has been illustrated that acne have tremendous effect on an individual’s self-image and impacts his or her quality of life. The extent of burden of the disease experienced by the patients seems to be underestimated by the whole medical fraternity. The aim of the study is to determine the health related quality of life impairment in acne patients using CADI and to identify various variables that increase the patients’ susceptibility for quality of life impairment. Subjects and Methods: This is a hospital based, cross sectional study conducted in the Department of Dermatology, Nobel Medical College Teaching Hospital from Jan 2017 to December 2017.A total of 202 acne patients were evaluated with CADI. Clinical characteristics were recorded after history and clinical examination. Results: Out of total 202 patients enrolled, 56.4% of patient scored a CADI score of (5-9) indicating moderate quality of life impairment and 15.3% of patient scored a CADI score of 10 or more indicating severe quality of life impairment. The mean CADI score was 6.82 ± 2.75. There was positive correlation between the CADI score and impact on quality of life with grade of acne, which was statistically significant (p